Furosemide administration results in a transient alteration in calcium balance in mature horses. Issue 3 (18th March 2020) - Pritchard, Abby; Nielsen, Brian D.; Robison, Cara; Spooner, Holly
Abstract: Previous research documented that furosemide negatively impacted calcium balance for 3 days but did not determine when calcium balance returned to baseline. This study hypothesized that furosemide's impact on calcium would return to control values before 7 days post‐administration. Ten mature geldings were assigned to either control (CON, n = 5) or treatment (FUR, n = 5) for the first of two 8‐day total collections in crossover design. Treatment horses received one administration of furosemide (1 mg/kg, IV). A 10% sample of pooled faeces and urine from each day was kept. Calcium concentrations in hay, faeces and urine were determined by an atomic absorption spectrophotometer. Data were analysed using mixed‐model‐repeated measures ANOVA to determine influence of day and treatment. For urine output, FUR urinated twice as much during the 24 hr after administration than CON ( p < .001). Horses in FUR excreted more urinary calcium 24‐hr post‐administration as compared to CON (9.3 ± 1.0 and 4.2 ± 1.0 g, respectively; p < .001). Calcium balance in FUR was more negative on day 1 than day 3 ( p < .05). Faecal calcium concentrations remained the same from day 1 to day 7 in CON (6.3 ± 1.3 and 5.5 ± 1.3 g/kg, respectively; p > .10) but were lower in FUR on day 7 as compared to day 1 (4.8 ± 1.3 and 7.3 ± 1.3 g/kg, respectively; p < .001), indicating a potential mechanism to restore calcium balance. These findings corroborate previous studies on furosemide and calcium balance and provide evidence for a possible mechanism to recover net calcium losses after furosemide administration. Since calcium balance returns to baseline in 3 days and previous results have examined frequent, long‐term use, furosemide may not negatively impact bone mineral content even if used over long periods.